Adaptive Housing as an Alternative Strategy for Fisher Settlement Planning in the Context of Coastal Sea Wall Development and National Resilience - Yanda Dwira Firman Z.; Susilo Adi Purwantoro (Yayasan Darussalam Bengkulu, 2026)
Coastal settlements along the northern coast of Java face escalating environmental pressures due to tidal flooding, land subsidence, and sea level rise. While sea wall development has been widely implemented as a macro-scale mitigation strategy, it remains insufficient in addressing vulnerabilities at the settlement level, particularly within informal fishing communities. This study examines adaptive housing as an alternative strategy for coastal settlement planning and evaluates its contribution to regional resilience and national defence. An embedded mixed-method approach was employed, combining qualitative analysis with quantitative data collected from 100 respondents in Muara Angke, North Jakarta. The findings reveal that adaptive housing through elevated and floating structures significantly reduces structural damage, lowers flood exposure, and improves access to clean water and sanitation. Community participation also increased substantially, indicating strengthened social resilience. In addition, the use of modular construction enhances efficiency in both time and cost. This study proposes the Integrated Coastal Settlement Resilience Model (ICSRM), which integrates macro-level infrastructure, micro-level adaptive housing, and community capacity as a unified resilience framework. The results demonstrate that adaptive housing not only improves environmental and socio-economic conditions but also contributes to territorial resilience within the broader context of non-military national defence. The study highlights the importance of multi-scalar integration in achieving sustainable coastal resilience.